The Entrepreneurial Decision: Economic Theory and Empirical Evidence - Eisenhauer, Joseph G. (Entrepreneurship Theory and Practice, 1995)
This paper Integrates three major traditions of economic thought into a model of entrepreneurial decision making. Several testable hypotheses are formulated, and the model Is estimated using a 33-year sample of aggregate time-series data for the U.S.